2004
DOI: 10.1111/j.1365-313x.2004.02318.x
|View full text |Cite
|
Sign up to set email alerts
|

Differing requirements for the Arabidopsis Rad51 paralogs in meiosis and DNA repair

Abstract: SummaryIn addition to the recombinase Rad51, vertebrates have five paralogs of Rad51, all members of the Rad51-dependent recombination pathway. These paralogs form two complexes (Rad51C/Xrcc3 and Rad51B/C/D/ Xrcc2), which play roles in somatic recombination, DNA repair and chromosome stability. However, little is known of their possible involvement in meiosis, due to the inviability of the corresponding knockout mice. We have recently reported that the Arabidopsis homolog of one of these Rad51 paralogs (AtXrcc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
201
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(214 citation statements)
references
References 78 publications
10
201
2
Order By: Relevance
“…RAD51 and its homologs build a small gene family in Arabidopsis similar to other eukaryotes (Lin et al , 2006). Previous studies revealed hypersensitivity of mutants in Arabidopsis RAD51 family members to DNA‐cross‐linking agents such as cisplatin and mitomycin C, as seen, for example, by a reduced number of true leaves formed in rad51b and rad51c mutants in comparison with the wild type (Osakabe et al , 2002, 2005; Bleuyard & White, 2004; Abe et al , 2005; Bleuyard et al , 2005; Li et al , 2005; Charbonnel et al , 2010). Consistent with these reports, we found that the root growth of rad51 mutants is impaired in the presence of cisplatin (Fig 5A–C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAD51 and its homologs build a small gene family in Arabidopsis similar to other eukaryotes (Lin et al , 2006). Previous studies revealed hypersensitivity of mutants in Arabidopsis RAD51 family members to DNA‐cross‐linking agents such as cisplatin and mitomycin C, as seen, for example, by a reduced number of true leaves formed in rad51b and rad51c mutants in comparison with the wild type (Osakabe et al , 2002, 2005; Bleuyard & White, 2004; Abe et al , 2005; Bleuyard et al , 2005; Li et al , 2005; Charbonnel et al , 2010). Consistent with these reports, we found that the root growth of rad51 mutants is impaired in the presence of cisplatin (Fig 5A–C).…”
Section: Resultsmentioning
confidence: 99%
“…A second hint for a role of HR in DSB repair comes from the observation that the cdkb1;1 cdkb1;2 double mutant was also sensitive to BLM (see above, Fig 4F and L). In addition, mutants in the plant RAD51 family are well known to be sensitive to DSB‐inducing drugs such as BLM and MMC (Bleuyard et al , 2005; Da Ines et al , 2013b; Wang et al , 2014). Previous studies have shown that NHEJ is the most prominent repair mechanism in plants and hence a role of CDKB1‐CYCB1 complexes in DSB repair might be largely masked by a very efficient execution of NHEJ (Knoll et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The osrpa1a Mutants Are Hypersensitive to DNA Mutagens Many mutants of genes related to DNA metabolism are hypersensitive to DNA mutagens such as mitomycin C (MMC), methyl methanesulfonate (MMS), and UV irradiation (Garcia et al, 2003;Bleuyard and White, 2004;Bleuyard et al, 2005;Waterworth et al, 2007). In yeast and human, RPA is involved extensively in various DNA repair pathways (Wold, 1997;Iftode et al, 1999).…”
Section: Meiosis In Pollen Mother Cells Is Affected In Osrpa1a Mutantsmentioning
confidence: 99%
“…Arabidopsis has a RAD51B homolog, named AtRAD51B. The atrad51b mutant is fertile, undergoes normal meiosis, and normal vegetative growth under standard growth conditions [109,110]. The atrad51b mutant exhibits moderate sensitivity to DNA-damaging agents, including gamma-radiation and cisplatin, indicating that the function of RAD51B is less important in plant mitosis, possibly because homologous recombination is less active in plants.…”
Section: Rad51 Paralogs In Animals and Plants: Rad51b Rad51c Rad51dmentioning
confidence: 99%
“…The authors proposed that because Drosophila lacks a detectable homolog of DMC1, it is possible that Drosophila RAD51C and XRCC3 (see below) function together in a pathway specific for meiosis as a replacement of the DMC1 function. In Arabidopsis, which has a DMC1 homolog, RAD51C is critical in meiosis and a mutation in this gene causes striking fragmentation of meiotic chromosomes visible starting at the end of prophase I, suggesting that Arabidopsis RAD51C is critical for processing meiotic DNA breaks [31,109]. Furthermore, homologous chromosomes in atrad51c fail to undergo synapsis and homolog juxtaposition [31].…”
Section: Rad51 Paralogs In Animals and Plants: Rad51b Rad51c Rad51dmentioning
confidence: 99%